Forehead flap reconstruction for post traumatic nasal defects: functional and aesthetic outcomes - Vashistha, Aakansha; Jain, R. K.; Garg, Paheli; Verma, Kush (International Surgery Journal, 2023)
The nose being the central unit is an important structure with a social and psychological significance. The reconstruction of nasal defects is complex as it involves the reconstruction of three separate structural layers which should be properly restored to maintain a functional nasal airway and an acceptable appearance. In this study, the aim was to reconstruct the 3D contour, border, outline and symmetry of the nose in post-traumatic defects with a forehead flap cover. A prospective study was conducted in the department of plastic and reconstructive surgery, over 3 years, 20 patients with post-traumatic nasal deformity were included in the study. The defects were categorized based on the subunits involved. The parameters recorded were age, sex, mode of injury, existing co-morbidities, habit of smoking and alcohol, any previous scar on the forehead, and history of previous surgery. Twenty patients underwent resection, out of which 13 (65%) were males and 7 (35%) were females using a para-median forehead flap cover. The most common mode of injury was road traffic accident in 12 (60%) cases, followed by animal/human bite in 5 (20%) cases and sharp cut injury in 3(15%) cases. (50%) patients required an intermediate stage after 3 weeks in which flap thinning was done with or without cartilage placement. Complications included suture dehiscence in one case for which re-suturing was done. 60% of patients were very satisfied with the results, and only 1 patient was unsatisfied. The forehead flap is a reliable choice for reconstruction in post-traumatic defects due to excellent color and texture match. Immediate reconstruction can be done in all the patients after adequate debridement under antibiotic coverage. Full thickness defects including the lining can be easily addressed by folding the flap.